The Use of Mobile Assisted Language Learning To Improve English Grammar for Senior High School Students - Maharani, Redyta Zalfa; Degeng, Putu Dian Danayanti; Razali, Khairil Azwar (Universitas Pendidikan Mandalika, 2024)
Mobile Assisted Language Learning (MALL) focuses on the mobility learning technology. The Utilizing of Mobile Assisted Language Learning (MALL) holds important role to improve effectiveness, flexibility, and convenience of learning. This research aims to explore Mobile Assisted Language Learning (MALL) which can enhance students’ grammar skills using Duolingo. It was conducted in Widyagama Senior High School in Malang. The respondents are 53 students wich consists 38 of class X and 15 of class XI B understudies who are utilizing Duolingo. To acquire data, The researcher used a Qualitative-Descriptive method by collecting data using questionnaires with Google Form and structured interviews. Data was collected employing a six-point Likert Scale questionnaires. As for the interviews, six questions were asked to obtain significant and substantial supporting research data. The results showed that more than 93% of students responded positively to this method which was considered effective to develop their knowledge, understanding, motivation and the effectiveness of Duolingo as a learning media to improve English grammar skills in the classroom. The research result appears that most of them deliver positive discernments about the application since they are simple to get the materials, they are more energized and persuaded in learning. Therefore, Technology-Based Learning using Duolingo is considered an appropriate method for English learning in senior high school. Mobile Assisted Language Learning (MALL) implementation can be optimized and can be improved in the future. This research is expected to provide new insights and can be applied in learning.